Chapter: 'Nurturing Communities of Inquiry: A Formative Study of the DojoIBL Platform' from book: Adaptive and Adaptable Learning: 11th European Conference on Technology Enhanced Learning, EC-TEL 2016, Lyon, France, September 13-16, 2016, Proceedings - Stefaan Ternier (Lecture Notes in Computer Science, 2016)
This formative study introduces DojoIBL, a web-based platform to support collaborative inquiry-based learning processes. By supporting communication and collaboration with new technological affordances, DojoIBL aims at nurturing communities of inquiry. The study elaborates on the theoretical underpinning of DojoIBL, describes its added value and presents a detailed explanation about the functionalities supported. Thereafter, an evaluation about how users perceived DojoIBL has been performed. Besides, the positive acceptance of participants, the results also showed that DojoIBL seems to be a suitable tool to support essential components of communities of inquiry. The study concludes anticipating the integration of role support as future developments of DojoIBL.